Evaluating competition in the Internet's infrastructure: a view of GAFAM from the Internet exchanges. Issue 1 (2nd January 2020) - Sowell, Jesse H.
ABSTRACT: The Internet has given rise to online platforms offering unrivalled access to diverse markets and services. At the application-layer, consolidation and concentration is framed as a threat to competition and diversity, with dominant players facing antitrust challenges in the US and the EU. Within the infrastructure though, concentration creates economies of scale that makes many of the resource-intensive building blocks of the Internet economy – such as global content delivery and distributed hosting – available to even the smallest innovator. This work complements existing analyses by exploring the links between these layers, differentiating between the implications of application-layer consolidation and the efficiencies of concentration at lower layers of the Internet's infrastructure. In particular, these differences are presented from the vantage point of Internet exchanges, evaluating consolidation in terms of the distribution of these essential building blocks and how IXes' governance norms lower barriers to accessing these resources. While promising, the spectre of predatory practices at the application layer remains. This article concludes by arguing that the indicators presented here highlighting regulatory interventions must effectively account for the complex interdependencies among these platforms.